Axel Hamberg's Sarek research 1895-1933: Use of Invisible Sámi Assistants - Granqvist, Karin (Royal Institute of Technology, 2019)
The natural geographer Axel Hamberg (1863-1933) became the funder of the research in the mountain massif, Sarek, Sweden, the area known as Sweden’s last wild life area. He based his thesis on the research results from Sarek. He installed instruments for hydrographical and metrological measurements, as well as for sun hour registrations. However, he was only present in the summers/autumns, so to keep the measurements on an annual basis did he hire Sámi as research assistants. Lars Nilsson Tuorda (1858-1930) became the most hired one, and was employed as a regular for almost two decades. Tuorda made most of the annual registrations and measurements in the Sarek research, supervised logistics in the area, and became in charge of the financial aspect of the research organisation when Hamberg was not present. Tuorda’s responsibility was massive. In Hamberg’s published scientific works are the efforts made by Tuorda, and other extras and assistants, not mentioned. Tourda’s, and others’ jobs, were only revealed in Tuorda’s letters to Hamberg, and in Hamberg’s private field diaries. Hamberg made the efforts of his assistants invisible before the reading public, and the scientific community. This also means that Hamberg based his thesis on scientific works he did not all execute himself, leaving beside the knowledge his Sámi co-workers provided for him, knowledge that he was in great need of in his work in Sarek. My own research is to reveal the extent of the works and efforts made by Hamberg’s hired assistants, in particular Lars Nilsson Tuorda’s work in Hamberg’s Sarek research organisation.

Naturgeografen Axel Hamberg (1863-1933) inledde forskningen i den svenska massiven Sarek. Hambergs forskning var beroende på hjälp från ett antal Sámiska forskningsassistenter, bland annat Lars Nilsson Tuorda (1858-1930), vars roll var avgörande för Hambergs forskning. Den här studien utforskar bredden och vikten av de Sámiska forskningsassistenternas bidrag till Hambergs forskning i Sarek.
Axel Hambergs Sarekforskning 1895-1933: De osynliga Sámiska forskningsassistenterna - Axel Hambergs Sarekforskning 1895-1933: De osynliga Sámimedhjälpare
Keywords: communities; samhällen; HUMAN DIMENSIONS; SOCIAL BEHAVIOR; POPULATION; POPULATION SIZE; LAND USE/LAND COVER CLASSIFICATION; LAND USE CLASSES; LAND SURFACE; LAND USE/LAND COVER; LAND RESOURCES; GEOMORPHIC LANDFORMS/PROCESSES; GLACIAL LANDFORMS; TECTONIC LANDFORMS; LANDSCAPE; LANDSCAPE ECOLOGY; LANDSCAPE MANAGEMENT; TOPOGRAPHY; CONTOUR MAPS; Earth and environmental sciences; Miljö-, klimat- och geovetenskaper; attitude; attityd; History; Historia